Composição química e atividades antioxidante e biológica das frações clorofórmica e hidrometanólica do extrato da raiz de Cereus jamacaru DC. (Cactaceae) - Santana, Amanda Ferreira (2016)
Cereus jamacaruDC. is a species of Cactaceae used in folk medicine, popularly known as mandacaru. This study aimed to identify the metabolites classes quantify the phenolic content and flavonoids, evaluate the antioxidant activity, toxicity and pharmacological potential of chloroform fractions (FC) and hydromethanol (FHM) C. jamacaru root. The extracts were prepared by maceration and fractions are obtained by liquid-liquid partition. The classes of metabolites were detected by thin layer chromatography, in chemical developers. The content of phenolics, and flavonoids were determined by UV-vis spectrometry. The antioxidant activity was evaluated by the radical sequestration methods (DPPH) and β-carotene/linoleic acid. Acute toxicity and the effect on the central nervous system by route rod test was evaluated. The antinociceptive activity was determined in tests of writhing, formalin and hot plate. The anti-inflammatory activity was carried out by the paw edema induced by carrageenan. The presence of terpenes, steroids, flavonoids, phenolic acids and amino acids was detected in the fractions. FC showed higher content of phenolics and flavonoids, and best antioxidant activity FHM analyzed by methods. Through the toxicological evaluation, it is suggested that the fractions are non-toxic orally. Regarding the antinociceptive activity, fractions reduced (p<0,001) the number of writhes and licking time in the 1ª and 2ª stage, at all doses tested. Fractions increased heat to the latency time (p<0,01 and p<0,001) at all doses and times observed. The anti-inflammatory activity was detected in fractions (p<0,001) in all the doses and times observed. The fractions did not affect the coordination of the animals, besides their antinociceptive and anti-inflammatory properties, with central action mechanism indicia, also showing the reduction effect of acute inflammatory processes. It is expected from this study, promote greater public awareness for the conservation and sustainable use of this species.